1976
DOI: 10.1002/pen.760160805
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of vinyl chloride monomer migration from rigid PVC pipe

Abstract: Data on the solubility and diffusion of vinyl chloride monomer (VCM) in PVC resin powders have been combined with published solutions of Fick's diffusion equation to yield predictions of the amount and rate of loss of residual VCM (RVCM) from rigid PVC pipe under storage and service conditions. The principal factors controlling VCM migration are the initial VCM content, thickness of the PVC section, temperature, and the age of the PVC product. Analytic solutions are presented for RVCM loss from freshly extrude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…As an example, if one assumes a film thickness of 40 mils (0.1016 cm) and a diffusion coefficient of 2.0 X 10~12 cm2 [a typical value for migration of small molecules in glassy polymers (Berens and Daniels, 1976)], the plots in Figure 1 which describe the apparent fractional loss (M//MJ) as a function of the square root of apparent time (t 0 for given storage times can be calculated using eq 8 in conjunction with eq 3 or eq 4. A similar plot of apparent fractional loss as a function of dimensionless apparent time, ' b Dt'/t2, for given dimensionless storage times, 8 = Dta/£2, is presented in Figure 2.…”
Section: Mtmentioning
confidence: 99%
“…As an example, if one assumes a film thickness of 40 mils (0.1016 cm) and a diffusion coefficient of 2.0 X 10~12 cm2 [a typical value for migration of small molecules in glassy polymers (Berens and Daniels, 1976)], the plots in Figure 1 which describe the apparent fractional loss (M//MJ) as a function of the square root of apparent time (t 0 for given storage times can be calculated using eq 8 in conjunction with eq 3 or eq 4. A similar plot of apparent fractional loss as a function of dimensionless apparent time, ' b Dt'/t2, for given dimensionless storage times, 8 = Dta/£2, is presented in Figure 2.…”
Section: Mtmentioning
confidence: 99%
“…Figure 12 compares the effect of Biot number Bi and + on fractional migration for a partially reactive Fg. 8…”
Section: E-03mentioning
confidence: 99%
“…reactive migrants (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22). on the environment type (18,24,27).…”
Section: Introductionmentioning
confidence: 99%
“…xtensive studies have been carried out on the diffusion of heavy metals, vinyl chloride, and other organic chemicals from PVC pipe ( 1 4 ) . A. R. Berens and C. A. Daniels (5) studied the diffusion of residual vinyl chloride monomer (RVCM) from PVC pipe, calculated the diffusion constants, and correctly predicted that low RVCM pipe, 1 mg/kg (ppm), will not give detectable vinyl chloride monomer in water under any expected service conditions. Their study also showed that six-month-old pipe containing 22 mg/kg of RVCM in the pipe would yield less than 5pg/kg (ppb) vinyl chloride monomer in a water extract.…”
Section: Introductionmentioning
confidence: 98%